THE IMPLEMENTATION OF PICTURE-WORD INDUCTIVE MODEL (PWIM) STRATEGY IN TEACHING WRITING A RECOUNT TEXT : A Quasi-Experimental Study of Teaching Writing at One Public Junior High School in Bandung - Huda, Anggia Miftahul (2017)
This study analyze the junior high school students' writing by implementing Picture Word Inductive Model. This study aims to identify whether there is an improvement of students' proficiency in writing a recount text by applying PWIM. The research design used is the quasi experimental design. This study compared an experimental group that received PWIM as a teaching strategy and a control group that received direct instruction in writing. Both the experimental and the control group consist of 30 eight grade students of class VIII-2 and VIII-4 of SMPN 1 Bandung. The instruments that were employed in this study were pretest, posttest, and questionnaire. The findings from pretest and posttest were analyzed by independent t-test. The study found that the mean of the experimental group is 79,23 and the mean of the control group is 73,57. The t-test result was 0,002<0,05 is lower than the level of significance. This proves that the Ho is rejected and Ha is accepted, which means that there is significant difference of students' writing recount text after applying PWIM. The result of r value was 0.395 which is large in scale. The results reveal that PWIM strategy significantly influences the students' ability in writing a recount text. Since it offers many beneficial values for the students, PWIM strategy improves students' ability in writing recount text.;---Penelitian ini menganalisa tulisan siswa dengan menerapkan strategi Picture-Word Inductive Model (PWIM). Penelitian ini bertujuan untuk mengetahui apakah ada peningkatan kemampuan siswa dalam menulis teks recount dengan menerapkan strategi PWIM. Desain penelitian yang digunakan adalah desain eksperimen kuasi. Penelitian ini membandingkan kelompok eksperimen yang menerima PWIM sebagai strategi pengajaran dan kelompok kontrol yang mendapat instruksi langsung untuk menulis. Baik kelompok eksperimen maupun kelompok kontrol terdiri dari 30 siswa kelas delapan kelas VIII-2 dan VIII-4 dari SMPN 1 Bandung. Instrumen yang digunakan dalam penelitian ini adalah pretest dan posttest. Hasil dari pretest dan posttest dianalisis dengan menggunakan independent t-test. Hasil yang ditemukan adalah bahwa rata-rata nilai kelompok eksperimen adalah 79,23 dan rata-rata nilai kelompok kontrol adalah 73,57. Hasil uji t adalah 0,002 <0,05 lebih rendah dari tingkat signifikansi. Ini membuktikan bahwa Ho ditolak dan Ha diterima, yang berarti ada perbedaan yang signifikan dari penulisan teks recount siswa setelah menerapkan PWIM. Hasil nilai r adalah 0,395. Hal ini menunjukan bahwa strategi PWIM mempengaruhi kemampuan siswa dalam menulis teks recount. PWIM strategi memberikan nilai-nilai yang menguntungkan bagi siswa dalam menulis, strategi ini dapat meningkatkan kemampuan siswa dalam menulis teks recount.